2004
DOI: 10.1016/j.pcrj.2004.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Programme in Finland: High consensus between general practitioners and pulmonologists on the contents of an asthma referral letter

Abstract: Summary Aims:The purpose of the present study was to define quality criteria for an asthma referral letter using a national co-operative effort between general practitioners and pulmonologists. Methods: A consensus-seeking expert panel representing primary and secondary health care merged evidence from the literature and existing national and local asthma programmes to produce 19 provisional criteria to be included in an asthma referral letter. These criteria were contained within a national questionnaire revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The first European National Asthma Programme was the Finnish 10-year programme (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004), which has been the model for other European and non-European programmes. Results and several follow-up reports of the Finnish programme have been published previously [52][53][54][55][56][57][58][59]. Apart from the Finnish programme, results have only been published from the Polish [14,15] and Portuguese [17] programmes.…”
Section: Resultsmentioning
confidence: 99%
“…The first European National Asthma Programme was the Finnish 10-year programme (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004), which has been the model for other European and non-European programmes. Results and several follow-up reports of the Finnish programme have been published previously [52][53][54][55][56][57][58][59]. Apart from the Finnish programme, results have only been published from the Polish [14,15] and Portuguese [17] programmes.…”
Section: Resultsmentioning
confidence: 99%
“…These 22 referrals together with the characteristics of the referral letters, provide the basic information required for a protocol to identify suitable referrals and to inform GPs on the necessary information to include in a referral letter -for example, a recent chest radiograph report. A recent study on asthma referrals [10] has shown that it is possible to obtain…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous literature, consulting other specialists, and discussion within the group, the maximal acceptable standard of inadequacy (MAS standard) developed by Williamson [10] was set to 30%, which means that the study group was prepared to accept the maximum of 30% of the referral letters to be of poor quality. As criteria, the 14 previously derived [9] asthma‐specific criteria (Table 1) were used. An auditing manual was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study we presented systematic development of quality criteria for an asthma referral letter [9]. These criteria were derived from three components: evidence from the literature, consensus‐seeking panel discussions, and a national review.…”
Section: Introductionmentioning
confidence: 99%